PENGARUH TRANSACTIONAL LEADERSHP DAN TRANFORMATIONAL LEADERSHP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KINERJA KARYAWAN - Gazali Gazali; Zainurrafiqi Zainurrafiqi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
Leadership is concerned with achieving goals by increasing followers based on implementing a tactical plan. Transformational Leadership, Transactional Leadership and Organizational Citizenship Behavior require more attention in the SME context; thus, this study purpose to address this gap, expand the work on employee performance and contribute to the literature with new findings. Based on the line of thought above, this study aims to reveal the most effective leadership styles for the SME sector in Pamekasan and to understand how Transactional Leadership and Transformational Leadership impact Organizational Citizenship Behavior (OCB) and Employee Performance. This is expected to ensure employee achievement and organizational development and progress through the evolution of supervision in the SME sector in Pamekasan. This type of research is Explanatory Research. Data collection method trought interviews. The sampling technique used purposive sampling. The number of samples is 200 employee of SMEs in Pamekasan Regency, and uses data analysis, namely the Structural Equation Model (SEM) with AMOS software. The results of this study indicate that Transactional Leadership has a positive and significant effect on Organizational Citizenship Behavior, Transformational Leadership has a positive and significant effect on Organizational Citizenship Behavior and Organizational Citizenship Behavior positive and significant effect on employee performance.